Tacrine for Alzheimer's disease. - Qizilbash, N; Birks, J; López-Arrieta, J; Lewington, S; Szeto, S (2000)
BACKGROUND: Tacrine is one of the first drugs to be widely marketed for the loss of memory and intellectual decline in Alzheimer's disease. The alleged success of tacrine in the treatment of these symptoms has been heralded as confirmation of the cholinergic theory of Alzheimer's disease. However, the efficacy of tacrine for symptoms of dementia remains controversial. This is reflected by the low rate of prescription of tacrine in countries where it is approved and the lack of approval by several regulatory authorities in Europe and elsewhere. The uncertainty about the efficacy of tacrine is due to the difficulties in interpretation of the results from the clinical trials. The reasons for this are the small effects of tacrine compared to placebo for all outcomes; the high incidence of adverse events; the lack of benefit observed in several trials; the use of cross-over designs and their associated methodological problems in a disease like dementia; the use of different measurement scales to assess outcome in different trials; and the problem of high dropout rates. OBJECTIVES: To determine the clinical efficacy of tacrine for the symptoms of Alzheimer's disease. SEARCH STRATEGY: The Cochrane Dementia Group Register of Clinical Trials was searched using the terms 'tacrine', 'tetrahydroaminoacridine' and 'THA' (see the Group's search strategy for full details). SELECTION CRITERIA: All unconfounded, double-blind, randomized trials in which treatment with tacrine was administered for more than a day and compared to placebo in patients with dementia of the Alzheimer's type. DATA COLLECTION AND ANALYSIS: Data were extracted independently by two reviewers, pooled if appropriate and possible, and the pooled odds ratios (95%CI) or the average differences (95%CI) were estimated. Where possible, intention-to-treat data were used. MAIN RESULTS: This review produced no clear results. The results were compatible with tacrine producing improvement, no change or even harm for those with Alzheimer's disease. It was not possible to use many of the published results in a combined analysis. For measures of overall clinical improvement, the intention-to-treat analyses failed to detect any difference between tacrine and placebo (OR 0.87; 95%CI 0.61 - 1.23). Behavioural disturbance, as measured by the Alzheimer's Disease Assessment Scale-noncognitive, failed to detect any difference between tacrine and placebo (SMD -0.04; 95%CI -0.52 - 0.43). For cognition function, the effect of tacrine was not statistically significantly different from placebo for the MiniMental State Examination score (0-30; high =good) (SMD 0.14; 95%CI -0.02 - 0.30) and was barely statistically significantly in favour of treatment for the Alzheimer's Disease Assessment Scale-cognitive scale (SMD -0.22; 95%CI -0.32 - -0.13). Adverse events were not reported in a systematic way in the different trials, making formal comparison difficult. Raised serum liver enzymes was the major reason for withdrawal. The odds ratio for withdrawal due to an adverse event was significantly different from one, the control group experienced fewer events (OR 5.7; 95%CI 4.1-7.9). Gastrointestinal side effects (diarrhoea, anorexia, dyspepsia and abdominal pain) were the other major cause of adverse events and for withdrawal, and the odds ratio for withdrawal was also significantly different from one in favour of the control group (OR 3.8; 95%CI 2.8-5.1). No deaths were reported in any of the studies during the trial period, up to six months. REVIEWER'S CONCLUSIONS: This review provides no convincing evidence that tacrine is a useful treatment for the symptoms of Alzheimer's disease. However, as so few trials presented data in a format suitable for pooling, the results of this review may be modified when further data from all relevant trials are included. There is an urgent need for the independent evaluation of the data already existing in the trials but not accessible through published or grouped data. A